Optimalisasi Penjualan Produk dan Manajemen Keuangan Melalui Pengelolaan Akuntansi dan Website Penjualan Online Pada Usaha Permen Tradisional “Soba Padu” - Mukhlisulfatih Latief; Moh. Syafri Tuloli; Lanto Miriatin Amali (Universitas Negeri Makassar, 2020)
The partner of this Community Partnership Program (PKM) was a “Soba Padu” UKM. The objectives to be achieved in this service activity are (1) providing management / financial management assistance in making simple bookkeeping to partners and (2) providing promotional media and marketing / selling products in the form of a website as well as conducting training on the use of online sales websites to UKM partners